Oral Bullous Lichen Planus – A Case Report (Community Based Medical Journal, 2024)
Oral bullous lichen planus (BLP) is a rare and challenging variant of lichen planus affecting the oral mucosa. A 40-year-old female patient was diagnosed with Bullous lichen planus and treated with hydroxychloroquin, triamcinolone acetonide, levamisole, prednisolone and benzydamine oral rinse. Her main complaint was a burning feeling in her mouth that was linked to generalised pruritis, and skin lesions. The patient has not had any lesions during their year-long follow-up. The incidence of oral bullous lichen planus and its treatment are still poorly understood in Bangladesh. With regard to our local context, this report seeks to advance knowledge of this condition.  CBMJ 2024 January: vol. 13 no. 01 P: 98-101